2004
DOI: 10.1128/jb.186.6.1758-1768.2004
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Crystalline Bacterial Cell Surface Layer Protein SbsB and the Secondary Cell Wall Polymer of Geobacillus stearothermophilus PV72 Assessed by Real-Time Surface Plasmon Resonance Biosensor Technology

Abstract: The interaction between S-layer protein SbsB and the secondary cell wall polymer (SCWP) of Geobacillus stearothermophilus PV72/p2 was investigated by real-time surface plasmon resonance biosensor technology. The SCWP is an acidic polysaccharide that contains N-acetylglucosamine, N-acetylmannosamine, and pyruvic acid. For interaction studies, recombinant SbsB (rSbsB) and two truncated forms consisting of either the S-layerlike homology (SLH) domain (3SLH) or the residual part of SbsB were used. Independent of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
73
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 42 publications
4
73
0
Order By: Relevance
“…SPR data were fit to the heterogeneous ligand model, a model previously used to distinguish independent binding sites on biological macromolecules (32,33). Similar to fluorescence, fits of the data to this model quantified two binding sites as follows: a high affinity site with K D values in the low nanomolar range and a weak affinity site with K D values in the low micromolar range.…”
Section: Identification Of Fhud-binding Sites On Tonb By Phagementioning
confidence: 99%
“…SPR data were fit to the heterogeneous ligand model, a model previously used to distinguish independent binding sites on biological macromolecules (32,33). Similar to fluorescence, fits of the data to this model quantified two binding sites as follows: a high affinity site with K D values in the low nanomolar range and a weak affinity site with K D values in the low micromolar range.…”
Section: Identification Of Fhud-binding Sites On Tonb By Phagementioning
confidence: 99%
“…Molecular masses in kilodaltons are indicated on the left. Ϫ8 M), and high (K d ϭ 6.7 ϫ 10 Ϫ11 M) affinities have been described previously (15). Furthermore, for rSbpA , the minimal SCWP-binding form of the S-layer protein SbpA, three K d values corresponding to low (K d ϭ 2.4 ϫ 10 Ϫ2 ), medium (K d ϭ 3.0 ϫ 10 Ϫ8 ), and high (K d ϭ 1.2 ϫ 10 Ϫ11 ) affinities could be determined.…”
mentioning
confidence: 99%
“…In Bacillaceae, at least two types of mechanisms for the binding of S-layer proteins and SCWPs have been identified. The first one involves so-called S-layer homologous (SLH) domains and pyruvylated SCWPs (3,4,8,9,(14)(15)(16)(17)(19)(20)(21)(22) and was previously found to be widespread among prokaryotes (16). By using surface plasmon resonance (SPR) spectroscopy, it has been demonstrated that the SLH domain of the S-layer protein SbsB of Geobacillus stearothermophilus PV72/p2 shows specific affinity for the pyruvylated SCWP of this organism but that it does not bind to any other type of SCWP or to peptidoglycan (PG) or other heteropolysaccharides (15).…”
mentioning
confidence: 99%
See 2 more Smart Citations